THE RELATIVE ACCURACY OF MANAGEMENT EARNINGS FORECAST AND IPO PERFORMANCE - Yanthi Hutagaol; I Gusti Ayu Esika (Jurnal Keuangan dan Perbankan, 2011)
Prior studies show that IPO earnings forecasts are robustly related to the IPO initial market valuation and itsshort-run performance (i.e., Chen, Firth, and Khrisnan, 2001; How and Yeo, 2001; Li and McConomy, 2004;Keasey and McGuiness, 2008). This study investigates the impact of management earning forecasts on thelong run performance of IPOs in Indonesia Stock Exchange (IDX). It hypothesizes that the relative accuracy,which is revealed at the end of IPO year, will affect the pricing process in the market that in turn will affect theIPO 1 year performance. Unlike most prior studies, this study uses relative forecast bias, as the direction of thebias will have different impact on the IPO after-market performance. Using 94 IPOs that went public in 2000-2008 in IDX, this study finds some interesting results. In general, the sample shows an average of negativeforecast bias. The upward bias IPOs has a better 1-year performance than the downward bias IPOs. They alsoappear to have a higher initial performance. Finally, the cross section analysis result shows a robust evidenceto support the research hypothesis that the relative accuracy of management earnings forecast is positivelyrelated to the IPO 1-year performance.